Nubbe natural products, source of molecular diversity for the design of new anticancer agents - Valli, Marilia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Natural products are an important source for the design of new drugs. This thesis aimed at the identification of bioactive natural products to be used as models for the design of compounds with antitumor properties. The lack of organized data is still one of the drawbacks in the natural products and medicinal chemistry area. Therefore, the compilation of accessible data of secondary metabolites from plant species or other sources is of great value, especially for the identification of molecular leads. This fact inspired us to propose as first objective of this thesis, the creation of the NuBBE database (NuBBEDB) containing botanical, chemical, and biological information of the secondary metabolites obtained and published by NuBBE in 15 years. This database can be useful not only for the current research in natural products of the group, but for the scientific society interested in bioactive compounds, metabolomics, and dereplication. A scientific paper describing the creation of the database was published in the Journal of Natural Products in 2013. NuBBEDB compounds were used as molecular source for the virtual screening with the protein tubulin. Based on the results of the virtual screening the biological evaluation of selected compounds was performed with the protein tubulin, and cell migration assays (Wound Healing and Boyden Chamber). The results of the biological assays indicated a series of guanidines and piplartine as active compounds. Piplartine was selected to be a model for the design of new compounds because it inhibited cell migration and is described in the literature as cytotoxic and selective, an interesting profile for this project. A series of 5 analogue compounds were designed and synthesized aiming at a better understanding of structure activity relationship and improvement of the biological activity. The compound designed by molecular simplification showed activity in the cell...

Os produtos naturais são uma importante fonte de inspiração para o desenvolvimento de novos fármacos. O presente trabalho visou identificar produtos naturais bioativos que pudessem ser usados como modelo para o planejamento de novos compostos com propriedades antitumorais. A falta de dados organizados é ainda uma das dificuldades das áreas de produtos naturais e química medicinal. Portanto, a compilação de dados disponíveis sobre os metabólitos secundários sejam de espécies vegetais ou de outras fontes é de grande valor. Esse fato nos motivou a propor como primeiro objetivo deste projeto, a criação de uma base de dados contendo informações botânicas, químicas e biológicas dos metabólitos secundários obtidos e publicados pelo NuBBE durante 15 anos. A base de dados poderá ser útil não apenas para a pesquisa em química de produtos naturais atual do grupo, mas para todos interessados em estudos de planejamento de moléculas bioativas, metabolômica e dereplication, já que está disponível para acesso livre na internet. Um artigo científico descrevendo a criação da base de dados foi publicado na revista Journal of Natural Products em 2013. Os compostos da base de dados foram utilizados como fonte de moléculas para uma triagem virtual baseada na estrutura do receptor com a proteína tubulina para a identificação de moduladores dessa proteína. Baseado nos resultados de triagem virtual foi realizada a avaliação biológica in vitro das substâncias utilizando a proteína tubulina e ensaios de migração celular (wound healing e câmara de Boyden). Os ensaios biológicos indicaram uma série de guanidinas e a piplartina como principais compostos bioativos dentre os avaliados. A piplartina foi selecionada como modelo para o planejamento de novos compostos, pois apresentou relevante inibição de migração celular, além de estar descrito na literatura como citotóxico e...
Keywords: Quimica organica; Produtos naturais; Banco de dados; Natural products